Comparative Immunohistochemical Study of Hidroacanthoma Simplex and Clonal Seborrheic Keratosis With GATA3 and p63. (January 2022) - Lin, Chien-Yio; Kuo, Tseng-tong; Chang, Ya-Ching
Abstract : Abstract: Histopathologically both hidroacanthoma simplex (HS) and clonal seborrheic keratosis (CSK) are characterized by intraepidermal nests of tumor cells. Although they show subtle microscopic differences, they can be difficult to accurately differentiate. Previous immunohistochemical studies have been inconclusive. We conducted an immunohistochemical study with GATA3 and p63 on cases of HS and CSK tentatively identified by their microscopic appearances and cases of eccrine poroma and seborrheic keratosis as their respective controls. The clinical, histopathological, and dermoscopic findings of these cases were also reviewed. All cases of HS and poroma were negative for GATA3, whereas all cases of CSK and seborrheic keratosis were positive for GATA3. HS, CSK, and their controls were all positive for p63. Microscopic, clinical, and dermoscopic differences were also found between HS and CSK. Our study demonstrated that GATA3 is useful for differentiating HS from CSK. Our initial microscopic observations also proved to be reliable, but immunostaining with GATA3 is helpful for confirming the diagnosis or establishing the diagnosis of uncertain cases. Awareness of the clinical and dermoscopic features of these 2 entities could also avoid misdiagnosis based solely on pathological observation.